Pemberdayaan Masyarakat Desa Karangsari melalui Penguatan Literasi Digital UMKM, Edukasi Gizi Ibu dan Anak, serta Implementasi Teknologi Pupuk Organik - Abdullah, Dudung; Achmad Mahiri, Eli; Kurnadi, Engkun; Wida Rahmayani, Melia; Hernita, Nita (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Community empowerment is an important part of achieving sustainable socio-economic development in rural areas. Karangsari Village, located in Darma Subdistrict, Kuningan Regency, has great potential for community education, microbusinesses, and agriculture. However, the village's progress is hampered by the lack of digital literacy among MSME actors, dependence on chemical fertilizers, and poor nutritional knowledge among pregnant and breastfeeding mothers. Digital literacy training for MSMEs, nutrition training for pregnant and lactating mothers, digital literacy training for school students, and training in liquid organic fertilizer (POC) production are all structured methods used to implement this community service program. The implementation methods include field observations, identification of partner needs, focused group discussions, scheduled training, and ongoing mentoring. The program results show a significant increase in the digital capabilities of MSMEs, family nutrition understanding, and community knowledge of environmentally friendly agricultural technology. This program proves the effectiveness of integrated empowerment activities and serves as a model for sustainable community development in rural areas.